2013
DOI: 10.1021/bi4007918
|View full text |Cite
|
Sign up to set email alerts
|

Local Control of cis-Peptidyl–Prolyl Bonds Mediated by CH···π Interactions: The Xaa-Pro-Tyr Motif

Abstract: Compared to generic peptide bonds, the peptidyl-prolyl bond shows a strong propensity for the cis conformer. The presence of a sequence-contiguous aromatic (Aro) residue can further stabilize the cis conformer, as observed for the Aro-Pro motif. The cis propensity of the reverse sequence motif, Pro-Aro, is not so well understood, especially the effect of N-capping the Pro-Aro motif with different amino acid residues. From a comparative nuclear magnetic resonance study of two peptide series with the general seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Immunoscreening of Peptides-Peptides corresponding to predicted B-cell epitopes were either chemically synthesized using an Endeavor 90-II peptide synthesizer (AAPTec, Louisville, KY) as described (44) or purchased from GL Biochem (Shanghai, China). For ELISA, 5 M each of synthetic peptides (P1-P5), rRhi o 1, HSA, and a random irrelevant oligopeptide were reconstituted in binding buffer (40 mM Na 2 CO 3 , 60 mM NaHCO 3 , 10 mM CaCl 2 , 10 mM DTT, pH 9.6) and separately coated on polystyrene plates.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoscreening of Peptides-Peptides corresponding to predicted B-cell epitopes were either chemically synthesized using an Endeavor 90-II peptide synthesizer (AAPTec, Louisville, KY) as described (44) or purchased from GL Biochem (Shanghai, China). For ELISA, 5 M each of synthetic peptides (P1-P5), rRhi o 1, HSA, and a random irrelevant oligopeptide were reconstituted in binding buffer (40 mM Na 2 CO 3 , 60 mM NaHCO 3 , 10 mM CaCl 2 , 10 mM DTT, pH 9.6) and separately coated on polystyrene plates.…”
Section: Methodsmentioning
confidence: 99%
“…Hα ( i – 2)- cis -proline–aromatic interactions may occur with the Hα of any residue two residues prior to ( i – 2 to) the aromatic residue but are most favorable with proline. 20 (c) Conformational heterogeneity in proline-rich sequences (PPFPP) due to multiple aromatic–proline interactions. Additional cis – trans isomerism is possible at other X-Pro sequences.…”
mentioning
confidence: 99%
“…In this work we have focused on cis Pro present at helix N‐termini. As elaborated earlier, the origin of the work was laid out in a previous study on short peptides …”
Section: Discussionmentioning
confidence: 99%
“…Previous NMR studies from our laboratory, performed on a series of three‐residue peptides with the general sequence Xaa‐Pro‐Tyr showed that the cis Pro conformation is stabilized in the motif through CH ⋅⋅⋅ π interaction when Xaa = Ala, Gly, Pro, Tyr, Phe and Trp. Although the experimental result correlated well with trends observed in protein structural database, Xaa = Glu was an exception.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation